Determinants of Strategic Factors for Digital Transformation in Micro and Small Enterprises in Makassar City - Tajuddin, Imran; Mahmud, Amir; Syahnur, Muhammad Haerdiansyah (Faculty of Economic and Business Syarif Hidayatullah State Islamic University of Jakarta, 2023)
The Indonesian government aims to promote information and communication technology (ICT) among micro and small enterprises to enhance their competitiveness in the global market. A survey was conducted among 180 micro and small enterprise owners in Makassar City using the Unified Theory of Acceptance and Use of Technology (UTAUT) model. The results showed that Performance Expectancy (PE) and Effort Expectancy (EE) insignificantly affect the Behavioral Intentions (BI) of the enterprise owners. It also indicated that Social Influence (SI) and Facilitating Conditions (FC) positively influence the adoption of ICT in micro and small enterprises. This study is novel and significant as it addresses a gap in the literature on digital transformation strategies, particularly in Makassar City, where such investigations are rare. Consequently, this study presents an original contribution to the field.JEL Classification: M2, O3, R2How to Cite:Tajuddin, I., Mahmud, A., & Syahnur, M. H. (2023). Determinants of Strategic Factors for Digital Transformation in Micro and Small Enterprise in Makasar City. Signifikan: Jurnal Ilmu Ekonomi, 12(1), 131-144. https://doi.org/10.15408/sjie.v12i1.31070.